Biomarker distributions and stable isotopes (C, S, H) to establish palaeoenvironmental change related to the end-Permian mass extinction event - Nabbefeld, Birgit (Curtin University, 2009)
Extinction, the irreversible loss of species, is perhaps the most alarming symptom of the ongoing biodiversity crisis. Some of the most significant changes in evolution throughout Earth’s history have coincided with extinction boundary events. In this thesis various organic geochemical (biomarker and stable isotopes) and geological (sedimentology and palaeontology) approaches have been undertaken to examine one of the most significant mass extinction events that occurred during the Late Permian (252 My ago) near to the Permian/Triassic (P/Tr) boundary. In the marine realm 49% of invertebrate families became extinct (equivalent to 80–96% of species loss). However, identifying an ecological crisis and associated extinction interval in any given extinction boundary section can often be difficult.Many different hypotheses have been proposed to explain the end-Permian extinction. The coincidence in timing of the extinction with the massive volcanic eruptions in Siberia has been established. The release of methane and possibly other gases during the volcanic event could have led to global warming. The oceans were oxygen deficient leading to euxinic conditions (with H[subscript]2S as a toxic agent) possibly triggering the extinction. Further, the selectivity of the extinction suggests hypercapnia (high CO[subscript]2) as a kill mechanism. It is widely accepted that the extinction is a “tangled web of causality” with several mechanisms contributing to the biotic crisis.Analyses of molecular fossils (biomarkers) and their stable isotopic compositions provide an alternative tool for identifying mass extinction intervals complimenting bulk stable isotopic data (δ[superscript]34Spyrite, δ[superscript]13Ccarbonate, δ[superscript]13Corg), sedimentological and fossil record data. Only recently have biomarker abundances (and δ[superscript]13C) and changes associated with the end-Permian extinction attracted significant attention. For example, biomarkers ultimately derived from pigments of organisms carrying out anoxygenic photosynthesis (Chlorobiaceae) have been recently reported in several P/Tr sections, providing evidence for widespread photic zone euxinic conditions.The aims of this PhD thesis were (i) to establish the palaeoenvironmental conditions associated with the P/Tr mass extinction event using an integrated biomarker, isotopic (including δD of biomarkers) and sedimentological approach for one section from the northern hemisphere and (ii) to establish whether the biomarker and isotopic signals (including δD of bulk kerogen) observed in several sections from about the globe represent localised environments of deposition and/or are related to global depositional conditions.In Chapter 2 for the first time an integrated study including sedimentological data, biomarker distributions/abundances and selected stable carbon and hydrogen isotopes along with bulk isotopes (δ[superscript]34Spyrite, δ[superscript]13Ccarbonate, δ[superscript]13Corg) for a Late Permian section from Lusitaniadalen, Spitsbergen, Norway has been conducted. These data support a marine transgression and collapse of the marine ecosystem in the Late Permian. Strong evidence for waxing and waning of photic zone euxinic conditions throughout the Late Permian section is provided by Chlorobiaceae-derived biomarkers (including δ[superscript]13C data) and δ[superscript]34Spyrite, suggesting several events of H[subscript]2S outgassing and potentially several pulses of extinction. A rapid decrease in abundance of various land plant biomarkers prior to the marine collapse event suggests a decline in terrestrial organisms during the Late Permian and/or increasing distance from the palaeoshoreline as an effect of sea level rise. Changes in δD of biomarkers also indicate a change in source of OM, microbial diversification and sea level rise. Further, compound specific isotope analysis (CSIA) data of algal and land-plant derived biomarkers, δ[superscript]13Ccarbonate and δ[superscript]13Corg provide strong evidence for synchronous changes in δ[superscript]13C of marine and atmospheric CO[subscript]2, attributed to a [superscript]13C-depleted source. The source could either be associated with isotopically depleted methane released from the melting of gas clathrates and/or from respired OM, due to the collapse of the marine ecosystem.In Chapter 3 δD of kerogen (δDkerogen) for three P/Tr sequences (Hovea#3, Perth Basin, Western Australia; Schuchert Dal section, Jameson’s Land, East Greenland and Lusitaniadalen, Spitsbergen) have been measured and compared with δ[superscript]34S of total reduced inorganic sulfur (δ[superscript]34Spyrite) of all three sections and for one sample set δ[superscript]13C of carbonate (δ[superscript]13Ccarbonate) to establish (i) similarities between the sections and (ii) evaluate whether these signals are local or global. Stable isotope shifts occur for all localities either at the P/Tr transition (Western Australia) or coinciding with the marine ecosystem collapse (Spitsbergen and East Greenland). δDkerogen reflects OM/kerogen type. Reliable palaeoenvironmental information in terms of the use of δD can therefore only be obtained for the P/Tr transition from hydrogen compound-specific isotope analyses of biomarkers (Chapter 2). The negative shifts in δ[superscript]13Ccarbonate (primary) and δ[superscript]13Ckerogen are attributed to the release of [superscript]13C-depleted carbon into the atmosphere, whereas the isotopic excursions in δ[superscript]34Spyrite relate to global palaeoredox changes. However, the global synchronous shifts in δDkerogen, δ[superscript]34Spyrite and δ[superscript]13Ckerogen for all sections suggest a relation between the sulfur, carbon and hydrogen cycles.In Chapter 4 the abundances of several polycyclic aromatic hydrocarbons (PAHs) throughout three P/Tr sections from the Global Stratotype Section and Point (GSSP) in Meishan (South China), Kap Stosch Area (East Greenland) and Peace River Basin (Western Canada) were evaluated. The PAHs dibenzothiophene and dibenzofuran were found to decrease in abundance just before or shortly after the P/Tr boundary in all three sections, supporting the hypotheses of a worldwide decrease in preservation of terrestrial OM. Perylene was observed in high abundance at the onset of the main extinction horizon (at bed 25) in Meishan and has been attributed to a wood degrading fungal source, consistent with the demise of land plants. Frequently occurring forest fire events are also evident from the abundance of several combustion-derived PAHs showing independent patterns in all sections. The coincidence of high abundances of combustion markers occurring simultaneous with ash beds in Meishan section indicates an origin related to the Late Permian and Early Triassic volcanic eruptions in Siberia and China.In Chapter 5 an evaluation of selected biomarker maturity parameters [methylnaphthalene ratio (MNR), methylphenanthrene index (MPI-1), C27 diasterane/sterane ratio and Ts/(Ts+Tm) ratio] has been conducted for a number of P/Tr samples (Western Australia, East Greenland and Spitsbergen). Differences in these parameters have been observed between freely extractable bitumens from sedimentary rocks (Bitumen I) and bitumens comprising hydrocarbons closely related to the kerogen/mineral matrix (Bitumen II). Further, a distinct connection between these differences and the clay/TOC ratio of the sediments has been made. The information on thermal maturity that is preserved within Bitumen II could be of significance in petroleum exploration studies, as the original thermal maturity signal of Bitumen I may be overprinted by migrated bitumen.